2015
DOI: 10.1007/s00122-015-2640-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of haplotypes at the Rsv4 genomic region in soybean associated with durable resistance to soybean mosaic virus

Abstract: Discovery of new germplasm sources and identification of haplotypes for the durable Soybean mosaic virus resistance gene, Rsv 4, provide novel resources for map-based cloning and genetic improvement efforts in soybean. The Soybean mosaic virus (SMV) resistance locus Rsv4 is of interest because it provides a durable type of resistance in soybean [Glycine max (L.) Merr.]. To better understand its molecular basis, we used a population of 309 BC3F2 individuals to fine-map Rsv4 to a ~120 kb interval and leveraged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…It was identified in soybean cultivars V94-5152 and mapped to a 0.4 cM interval between the proximal marker Rat2 and the distal marker S6ac, in a ∼94 kb haplotype block on soybean chromosome 2 (MLG D1b++W) (Hayes et al, 2000; Saghai Maroof et al, 2010; Ilut et al, 2016). A haplotype phylogenetic analysis of this region suggests that the Rsv4 locus in G. max is recently introgressed from G. soja (Ilut et al, 2016). Interestingly, this interval did not contain any NB-LRR type R genes.…”
Section: Mapping Of Smv Resistant Locimentioning
confidence: 99%
See 1 more Smart Citation
“…It was identified in soybean cultivars V94-5152 and mapped to a 0.4 cM interval between the proximal marker Rat2 and the distal marker S6ac, in a ∼94 kb haplotype block on soybean chromosome 2 (MLG D1b++W) (Hayes et al, 2000; Saghai Maroof et al, 2010; Ilut et al, 2016). A haplotype phylogenetic analysis of this region suggests that the Rsv4 locus in G. max is recently introgressed from G. soja (Ilut et al, 2016). Interestingly, this interval did not contain any NB-LRR type R genes.…”
Section: Mapping Of Smv Resistant Locimentioning
confidence: 99%
“…Interestingly, this interval did not contain any NB-LRR type R genes. Instead, several genes encoding predicted transcription factors and unknown proteins are present within the region, suggesting that Rsv4 most likely belongs to a novel class of resistance gene (Hwang et al, 2006; Ilut et al, 2016). …”
Section: Mapping Of Smv Resistant Locimentioning
confidence: 99%
“…Moreover, linkage analysis revealed that the Rsc10‐r was mapped on chromosome 6 (Figure b), while that of in KF ( Rsc10 ) was located in the vicinity of Rsv4 on chromosome 2 (Li et al., ) (Figure d), of which resistance was probably attributed to an original class of disease resistance genes (Ilut et al. ; Maroof et al., ; Wang, Ma, Yang et al., ; Zhao et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Ilut et al. (), R SC8 and Rsv4 may be two different dominant resistance genes that are tightly linked in a region on chromosome 2. Analysis of Williams 82 soybean genome sequences in the 30.8‐kb region believed to represent the location of R SC8 revealed the presence of two possible transcription factor genes, Glyma.02G121500 and Glyma.02G121600.…”
Section: Discussionmentioning
confidence: 99%
“…Ilut et al. () further narrowed the likely location of the Rsv4 locus to an approximately 94‐kb haplotype block.…”
mentioning
confidence: 99%